A behavioral study of the nature of verb–noun dissociation in the nonfluent variant of primary progressive aphasia. Issue 2 (1st February 2019) - Beber, Bárbara Costa; Mandelli, Maria Luisa; Santos, Miguel Angel Santos; Binney, Richard J.; Miller, Bruce; Chaves, Márcia L. F.; Gorno-Tempini, Maria Luisa; Shapiro, Kevin A.
ABSTRACT: Background : Patients with nonfluent/agrammatic variant primary progressive aphasia (nfvPPA) have more difficulty producing verbs than nouns, but the reason for this discrepancy remains unclear. One possibility is that it results from impaired access to motor programs integral to semantic representations of actions. Another is that the disruption affects specific lexical or grammatical features of verbs. Aims : To use an oral picture naming task to examine the effects of motor associations on verb production in patients with nfvPPA. Methods & Procedures : We administered noun and verb naming tasks to 12 nfvPPA patients and 9 controls. We varied the manipulability of target items across categories as a proxy for the degree to which lexical access depends on motor knowledge. Outcomes & Results : Nonfluent PPA patients were significantly more impaired in both noun and verb naming compared to control participants. However, the nfvPPA patients were significantly more impaired in naming verbs than nouns, but there was no effect of manipulability. Conclusions : The results suggest that the verb naming deficit in nfvPPA is not directly related to impaired motor knowledge and is more likely to be related to other properties that distinguish verbs from nouns.